Renewable energy for sustainable development - Østergaard, Poul Alberg; Duic, Neven; Noorollahi, Younes; Kalogirou, Soteris A. (My University, 2022)
This review article addresses the status of research within the application of renewable energy sources. It focuses on the status of renewable technologies, the role of renewable energy sources in meeting sustainable development goals, the status of the research into the sustainability of the renewable energy systems, and finally on the integration of renewable energy technologies in low carbon energy systems. Regarding renewable resources and technologies, wind and wave power resource assessment, heating and cooling, solar energy, renewable energy fuels, and integrated energy systems are reviewed and summarized. The article takes a starting point in work presented at the conference series on Sustainable Development of Energy, Water and Environmental Systems (SDEWES), published in the Renewable Energy journal and puts this work into a broader context.
Keywords: Renewable energy; Sustainability; Technology; Green energy; Review